2013
DOI: 10.1088/1741-2560/10/5/056007
|View full text |Cite
|
Sign up to set email alerts
|

An online EEG BCI based on covert visuospatial attention in absence of exogenous stimulation

Abstract: Objective. In this work we present-for the first time-the online operation of an electroencephalogram (EEG) brain-computer interface (BCI) system based on covert visuospatial attention (CVSA), without relying on any evoked responses. Electrophysiological correlates of pure top-down CVSA have only recently been proposed as a control signal for BCI. Such systems are expected to share the ease of use of stimulus-driven BCIs (e.g. P300, steady state visually evoked potential) with the autonomy afforded by decoding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
48
2
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(57 citation statements)
references
References 30 publications
5
48
2
2
Order By: Relevance
“…Here, we show that a simple template matching approach yields performance comparable to other studies, both in terms of classification rate as well as information transfer rate per subtrial. On trial level, our paradigm yielded an average performance of around 66 % in the last session, which is in between the offline studies by van Gerven et al van Gerven et al (2009) and Kelly et al (2005) and the online study by Tonin et al (2013). On subtrial level, Subject 1 obtained a maximal information transfer rate of 8.9 bits/min which is comparable to the maximum ITR found by Kelly et al (7.5 In both paradigms, cueing one side was followed by a change in visual stimulation at that side.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…Here, we show that a simple template matching approach yields performance comparable to other studies, both in terms of classification rate as well as information transfer rate per subtrial. On trial level, our paradigm yielded an average performance of around 66 % in the last session, which is in between the offline studies by van Gerven et al van Gerven et al (2009) and Kelly et al (2005) and the online study by Tonin et al (2013). On subtrial level, Subject 1 obtained a maximal information transfer rate of 8.9 bits/min which is comparable to the maximum ITR found by Kelly et al (7.5 In both paradigms, cueing one side was followed by a change in visual stimulation at that side.…”
Section: Discussionsupporting
confidence: 64%
“…While these studies do suggest that modulations in alpha power can be used for BCI control, all studies relied on offline analyses after data acquisition. Recently, Tonin et al (2013) showed for the first time that covert attention brain-computer interfacing is possible using electronencephalography in an online setup.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Contrary to CVSA based BCI [27], [28], which enabled covert visual attention decoding without visual stimulation and especially without overt eye movement, in the somatosensory modality without physical tactile stimulation, the imagined sensation task has also induced oscillatory activation in the somatosensory area of the brain and enabled covert somatosensory attention decoding without any sensory input. Furthermore, during the SAO tasks, both in the STE-Group and SAO-Group, the contralateral ERD was stronger than the ipsilateral ERD, which is consistent with motor imagery studies (mentally simulated efferent output) [41] and tactile BCI based selective sensation (afferent input processing) [20].…”
Section: A Existence and Efficacy Of Sao Based Independent Bcimentioning
confidence: 99%
“…the focus of attention on different regions of the visual field without overt eye movements, it has been observed that selective activation of the parieto-occipital α oscillation reflects endogenous shifts in the locus of visual attention [27]. Moreover the endogenous brain activation from the CVSA task has been shown to allow construction of an independent BCI without visual stimulation and especially without overt eye movement [28], [29]. Therefore, it is possible that covert visual attention is decoded even without the presence of the visual stimulus.…”
mentioning
confidence: 99%